Pluralistic Collapse: The "Oil Spill" Model of Mass Opinion Polarization. Issue 3 (June 2020) - DellaPosta, Daniel
Despite widespread feeling that public opinion in the United States has become dramatically polarized along political lines, empirical support for such a pattern is surprisingly elusive. Reporting little evidence of mass polarization, previous studies assume polarization is evidenced via the amplification of existing political alignments. This article considers a different pathway: polarization occurring via social, cultural, and political alignments coming to encompass an increasingly diverse array of opinions and attitudes. The study uses 44 years of data from the General Social Survey representing opinions and attitudes across a wide array of domains as elements in an evolving belief network. Analyses of this network produce evidence that mass polarization has increased via a process of belief consolidation, entailing the collapse of previously cross-cutting alignments, thus creating increasingly broad and encompassing clusters organized around cohesive packages of beliefs. Further, the increasing salience of political ideology and partisanship only partly explains this trend. The structure of U.S. opinion has shifted in ways suggesting troubling implications for proponents of political and social pluralism.